Can you hear me? Music labels by visual artists - Spampinato, Francesco, 1978- (Eindhoven : Onomatopee, 2015)
Can You Hear Me? Music Labels by Visual Artists' is the first survey on the obscure and fascinating phenomenon of record labels founded and run by visual artists. It reflects on the way these extra-artistic activities contribute to redefining the role of the contemporary artist as a catalyst of intellectual energies and producer of cultural processes at large. Moreover, it tries to understand if and how these activities challenged the art world’s static and modern perception of art and art works. Spanning 1980 to 2015, the project consists in a book and an exhibition that celebrate the contemporary artist as a multi-facetted producer of collaborative projects. The highlighted labels have released a dynamic spectrum of activities in and outside the art world and remained untouched by its unwritten capitalist code, attempting to develop alternative forms of cultural production and attract new audiences.0Exhibition: Onomatopee Gallery Space, Eindhoven, The Netherlands (May 3 – May 23, 2015).
Limited edition of 1250 copies.
"Released during the Exhibition at Onomatopee Project Space, Eindhoven, May 2015"--Colophon.
RECORD LABELS FEATURED Arcangel Surfware, Avant/Savant, Awesome Vistas, Beige Records, Chicks on Speed Records, Compound Annex, D.S. al Coda, Decemberism, Distributed History, Duchess Archive, Earhole Productions, Elektro Music Department, Hyena, Kalup Linzy Studio, Leiterwagen, Make it Happen, Musicsystem, Nuevos Ricos, raster-noton, Synchronic, Tartown Record Co., Teenage Teardrops, Villa Magica, Von Archives, and Wierd.
ARTISTS FEATURED Carlos Amorales, Cory Arcangel, John Amrleder and Sylvie Fleury, Jean-Michel Basquiat, Johanna Billing, Matthew Brannon, Chicks on Speed, Paul B. Davis, Destroy All Monsters, Cali Thornhill Dewitt, Dexter Sinister, DJ Spooky, Chris Johanson, Mike Kelley, Kalup Linzy, Lucy McKenzie, Carsten Nicolai, Albert Oehlen. Daniel Pflumm, Seth Price, Pieter Schoolwerth, SUPERFLEX, Mika Tajima, Nico Vascellari, Andy Warhol, and Alex Waterman.
boek
Keywords: Sound recording industry -- Exhibitions; Artists -- Exhibitions